Female business faculty attrition: paths through the labyrinth. Issue 4 (13th May 2014) - Klemm Verbos, Amy; Vee E. Dykstra, De
Abstract : Purpose: – The purpose of this paper is to explore female business faculty perceptions about attrition from a business school to uncover factors that might assist in female faculty retention in business schools. Design/methodology/approach: – Using a qualitative study approach and guided by past literature, the paper systematically analyses open-ended responses to interview questions and notes emergent themes. Findings: – The major themes that emerged as factors leading to attrition: first, an exclusionary and managerialist culture which marginalized and demoralized women; second, curtailed career opportunities, including a lack of gender equity in promotion and tenure; third, poor leadership; and fourth, break up of a critical mass of women. The factors then that might assist in female faculty retention are a critical mass of women, gender equity, inclusive, collaborative cultures, psychological safety, and ethical leadership. The career patterns of the women indicated that a labyrinth is an apt metaphor for their career paths. Research limitations/implications: – This research examines just one school from the perspective of women who left. It holds promise as the basis for future studies across business schools and to faculty within business schools to determine whether the emergent themes hold across schools. Originality/value: – This study examines women in business academe through the attraction-selection-attrition framework and by extending the labyrinth career metaphor to an academic setting. The paper also provides a conceptual model of female faculty retention.